Supercapacitive Properties of Nanocarbons Modified with Manganese Oxide Nanoparticles and Metallotetrapyrazinoporphyrazines - Ozoemena, Kenneth I. (University of Pretoria, 2021)
Dissertation (MSc)--University of Pretoria, 2013.